Chemotherapy may eradicate ductal carcinoma in situ (DCIS) but not the associated microcalcifications. Issue 8 (August 2017) - Goldberg, H.; Zandbank, J.; Kent, V.; Leonov-Polak, M.; Livoff, A.; Chernihovsky, A.; Guindy, M.; Evron, E.
Abstract: Introduction: We studied the effect of neoadjuvant chemotherapy (NAC) ± trastuzumab on the ductal carcinoma in situ (DCIS) component in patients with locally advanced breast cancer who achieved pathological complete response (pCR). Methods: The diagnostic biopsies of 92 consecutive breast cancer patients that were treated with neoadjuvant chemotherapy (NAC) ± trastuzumab were evaluated for the presence of DCIS. Upon completion of NAC, the surgical specimens were evaluated for complete eradication of both the invasive and non-invasive cancer in the breast. The pretreatment mammograms were evaluated for the presence of microcalcifications and compared to the mammograms that were obtained upon completion of therapy prior to surgery. Results: Thirty of 92 patients (33%) had a substantial component of DCIS in the pretreatment biopsy. Thirty nine patients (42%) achieved pCR: 22 (56%) following NAC + trastuzumab, 17 (32%) following chemotherapy only. Ten of 30 patients (33%) with DCIS component achieved pCR: 4 received chemotherapy only, in 6 trastuzumab was added. Multiple microcalcifications on the pretreatment mammograms were observed in 3 of 10 patients with DCIS who achieved pCR. No reduction in the area of calcifications was observed following NAC. Conclusions: DCIS may be completely eradicated by NAC ± trastuzumab. However, associated microcalcifications probably persist. Patients with locally advanced breast cancer with substantial DCIS may still opt for NAC and breast conservation as the DCIS component may respond and even completely disappear following NAC. Residual widespread microcalcifications after NAC do not necessarily indicate residual cancer. Larger studies are needed to direct the surgical management of these patients.